Alteração no perfil de expressão dos genes de folhas de Cajueiro CCP76 (Anacardium occidentale L.) em resposta ao estresse salino - Moreira, Raulzito Fernandes (2014)
Salt stress is touted as having negative impacts on the production of commercial cultivars interest. In recent years studies have focused on the research and understanding of the mechanisms used by plants to tolerate this kind of stress naturally. Among the species that tolerate salt stress is Anacardium occidentale L. or popularly known as Cashew. Studies in the literature have described the mechanisms that this cultivar can use to support the stress condition. However, additional studies to obtain an overall view of the process are required for a better understanding of the pathways that are involved in response to salt stress in Cashew. This study aimed to evaluate the global gene expression in leaves Cashew CCP76 based on transcriptomic profile in normal and stress condition. As such, there is induction of salt stress with 150 mM NaCl and collections of leaves were performed after 1, 3, 6 and 12 hours of salt addition. The leaves transcriptome assembled using the Velvet program. Finally, the data identified by the BLAST tool and were classified based on Gene Ontology (GO) and KEGG Pathways. The data were used in the comparative analysis between the plants in salt stress and control. A total of 9,133,193 and 10,787,002 reads were obtained for the control condition and stress, respectively. The results showed that contigs with covers greater than 50 times were related pathways for the production of amino acids, secondary metabolites and antioxidative enzymes. These results show metabolic changes undergone by the species under for adaptation to stress conditions. In short, it can be observed efficiently global changes in the metabolism of cashew for adaptation to stress condition. The results augment the information about possible routes that Anacardium occidentale L. uses to tolerate the stress condition, and also point to elucidate new mechanisms used by this organism. This is the first work in the literature that examined the impacts on transcripts in the early hours of salt stress on cashew.